Effects of employing in-service EFL teachers strategy-based instruction on their performance of teaching listening comprehension in Amman-Jordan - Al-Husban, Naima (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study investigated the effect of a proposed training program based on strategy-based instruction (SBI) on EFL female teachers' performance in teaching listening comprehension. The participants of the study were 36 EFL female teachers who were purposefully chosen by EFL supervisors from schools in Amman. The participants were randomly divided into two groups: 18 EFL teachers in the experimental group who were trained according to the proposed training program and 18 teachers in the control group who were received a conventional training program. A teaching listening comprehension scale and an observation checklist were used as research tools. Analysis of covariance (ANCOVA) was employed to identify any statistically significant differences between the two groups on teachers' performance in teaching listening comprehension. The findings revealed that the teaching performance in listening comprehension of female EFL teachers in the experimental group outperformed the control group, and employed most of the SBI when the participants were observed. Based on the results of the study, the researcher recommends that future research be investigated on the effect of research-based strategies on teacher effectiveness in teaching other language skills.